Experimental Investigation, Modeling, and Optimization of Wear Parameters of B4C and Fly-Ash Reinforced Aluminum Hybrid Composite - Sahu, Mohit Kumar; Sahu, Raj Kumar (Frontiers in Physics, 2020)
Lightweight and high wear performance materials are the current demand in various advanced applications like aerospace and automobiles. These demands can be achieved by hybrid aluminium matrix composites (HAMCs) as they possess excellent mechanical & tribological properties which can be customized using more than one reinforcements. Boron carbide (8wt.%) and fly-ash (2 wt.%) reinforced hybrid aluminium 7075 composite was successfully fabricated using a stir-casting route. Wear is a crucible phenomenon that occurs over the interaction of surfaces and affects the performance of the material. To investigate wear behaviour of developed HAMC, the dry sliding wear tests were conducted based on the central composite design taking the specific wear rate as a response parameter. Modelling of wear parameters is very crucial, as it helps to predict the value of the wear response at the given set of input parameters without performing experimentation. Response surface method (RSM) was used for the modelling of wear parameters to develop an empirical model of specific wear rate in terms of load, sliding speed and distance. The high value of the coefficient of determination (R2= 0.9894) illustrates the goodness of fit of the developed model. Moreover, the optimal condition of wear parameters was determined as 20 N load, 1.5 m/s sliding speed and 500 m sliding distance, the predicted value of specific wear rate in this set of parameters is 0.2×10-5 mm3/N-m. The validation test at optimal condition was performed and the specific wear rate is found as 0.205×10-5 mm3/N-m, which shows good agreement with the predicted value. The worn-out surface and debris were analyzed using scanning electron microscope (SEM) images and electron dispersive spectrum (EDS) to completely explore the mechanism of wear.